2015
DOI: 10.7314/apjcp.2015.16.14.6149
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Significance of VEGF and HIF-1α Expression in Patients with Metastatic Colorectal Cancer Receiving Chemotherapy Combinations with Bevacizumab

Abstract: Background: There is no suggested molecular indicator for the determination of which patients will benefit from anti-angiogenetic treatment in metastatic colorectal cancers. Materials and Methods: In this study, VEGF and HIF-1α expression and their clinical significance were studied in tumor tissues of patients with colorectal cancer receiving bevacizumab-based treatment. VEGF and HIF-1α were assessed by immunohistochemistry in the primary tumors of 53 metastatic colorectal cancer patients receiving chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…liver metastases tissues of 46 patients with mCRC were investigated and compared with the primary tumor. HIF-1α, VEGF and CD34 were positively expressed at both sites, indicating that they were closely associated with the occurrence and development of mCRC (25). Further research and analysis demonstrated no significant difference in the expression levels of HIF-1α and VEGF across different ages, sex, tumor sizes and degrees of histological differentiation.…”
Section: Discussionmentioning
confidence: 82%
“…liver metastases tissues of 46 patients with mCRC were investigated and compared with the primary tumor. HIF-1α, VEGF and CD34 were positively expressed at both sites, indicating that they were closely associated with the occurrence and development of mCRC (25). Further research and analysis demonstrated no significant difference in the expression levels of HIF-1α and VEGF across different ages, sex, tumor sizes and degrees of histological differentiation.…”
Section: Discussionmentioning
confidence: 82%
“…However, the expression of VEGF as a prognostic factor has been debatable. Ochs et al [55] suggested that the overexpression of VEGF was associated with poorer survival, while Berk et al [56] observed an improved PFS and OS in patients with high VEGF expression. In this regard, antiangiogenic treatments deserve further research.…”
Section: Molecular Background Of Mucinous Colorectal Adenocarcinomamentioning
confidence: 99%
“…It was investigated whether VEGF had predictive value in mCRC patients receiving bevacizumab; no significant difference was found. 21 CRC is the first malignancy where clear evidence was shown for the efficacy of anti-VEGF strategy in randomized trials. Recently, newly developed targeted therapies have led to significant improvements in the survival of metastatic CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a group with low expression of PDGF-BB, mOS was 21 months (95% CI [16][17][18][19][20][21][22][23][24][25][26], and in a group with high expression of PDGF-BB, mOS was 31 months (95% CI 5-57) (p ¼ 0.16).mOS was 26 months (Figure 2).…”
Section: Survival Analysis (Pfs Mos)mentioning
confidence: 99%